The Effect of Forest Management Initiatives on Sustainability of Forests: Evidence from Uganda - Niyongere, Pierre Celestin; Atukunda, Gershom; Muriisa Kabeba, Roberts (Journal of Popular Education in Africa, 2018)
The study looked at the effect of forest management initiatives on sustainability of forests in Isingiro District, South western Uganda. The study adopted a cross-sectional descriptive design and targeted district forestry and environment officials, local residents, local leaders (LC II-III) and environment committee representatives at local councils II & III in Isingiro district. Purposive and simple random sampling techniques were used to select respondents. Questionnaire and interviews were used as a data collection method. Data analysis used descriptive statistics in form of frequency and percentages while data from primary source particularly interview guide was compared, validated and confirmed with data from secondary sources. Findings from the field established that forest management has promoted sustainability of forests in the district through gazetting forest premises, existing forests being carefully monitored and proper land management being maintained. Sustainability of forests was being hindered by Limited resources for implementing forest management policies and negative perceptions towards forest management. Promoting sustainability of forests in Uganda is an enormous work that requires concerted efforts from all the different stakeholders. There is need to increase funding in the forestry department to enable the planners make plans and enforce them at up to the community level.
Keywords: Forest; Management; Initiatives; Sustainability